Why beautiful people have more daughters from dating, shopping, and praying to going to war and becoming a billionaire : two evolutionary psychologists explain why we do what we do - Miller, Alan S. 1926- (Perigee Book, 2008)
An analysis of the ways in which evolution shapes human behavior and human lives draws on the field of evolutionary psychology to offer revealing glimpses of human nature and to shed new light on why humans do the things that they do
Includes bibliographical references (p. [211]-239) and index
Introduction. Human nature "?" us -- The forgotten half of the equation -- Two errors in thinking that we must avoid -- A note about stereotypes -- How to use this book -- 1. What is evolutionary psychology? -- A typical view from the social sciences -- The evolutionary psychological perspective -- The Savanna principle : why our brains are stuck in the Stone Age -- 2. Why are men and women so different? -- What about culture? Is anything cultural? -- On to the puzzles and questions -- 3. Barbie, manufactured by Mattel, designed by evolution : the evolutionary psychology of sex and mating -- Why do men like blonde bombshells (and why do women want to look like them)? -- Why is beauty not in the eye of the beholder or skin-deep? -- Why is prostitution the world's oldest profession, and why is pornography a billion-dollar industry? -- Why Sean Connery and Catherine Zeta-Jones, but not Lauren Bacall and Brad Pitt? --
Keywords: Evolutionary psychology; Beauty, Personal / Psychological aspects; Sex differences (Psychology); Psychologie